Extract of Antrodia camphorata Exerts Neuroprotection against Embolic Stroke in Rats without Causing the Risk of Hemorrhagic Incidence - Ye-Ming Lee; Chiu-Yun Chang; Ting-Lin Yen; Pitchairaj Geraldine; Chang-Chou Lan; Joen-Rong Sheu; Jie-Jen Lee (The Scientific World Journal)
In this study, the neuroprotective effect of an extract of Antrodia camphorata (A. camphorata), a fungus commonly used in Chinese folk medicine for treatment of viral hepatitis and cancer, alone or in combination with aspirin was investigated in a rat embolic stroke model. An ischemic stroke was induced in rats by a selective occlusion of the middle cerebral artery (MCA) with whole blood clots and then orally treated with A. camphorata (0.25 and 0.75 g/kg/day) alone and combined with aspirin (5 mg/kg/day). Sixty days later, the brains were removed, sectioned, and stained with triphenyltetrazolium chloride and analysed by a commercial image processing software program. Brain infarct volume, neurobehavioral score, cerebral blood perfusion, and subarachnoid and intracerebral hemorrhage incidence were perceived. In addition, potential bleeding side effect of the combinative therapy was assessed by measuring hemoglobin (Hb) content during intracerebral hemorrhage and gastric bleeding, prothrombin time (PT), and occlusion time (OT) after oral administration. Posttreatment with high dose A. camphorata significantly reduced infarct volume and improved neurobehavioral score (P < 0.05). Since A. camphorata alone or with aspirin did not alter the Hb level, this treatment is safe and does not cause hemorrhagic incident. Remarkably, the combination of A. camphorata and aspirin did not show a significant effect on the bleeding time, PT and OT increase suggesting that A. camphorata may have the neuroprotective effect without the prolongation of bleeding time or coagulation time. From these observations, we suggest that combinative therapy of A. camphorata and aspirin might offer enhanced neuroprotective efficacies without increasing side effects.